Petroleum potential, thermal maturity and the oil window of oil shales and coals in cenozoic rift basins, central and Northern Thailand - H. I. Petersen (2018)
Oil shales and coals occur in Cenozoic rift basins in central and northern Thailand. Thermally immature outcrops of these rocks may constitute analogues for source rocks which have generated oil in several of these rift basins. A total of 56 oil shale and coal samples were collected from eight different basins and analysed in detail in this study. The samples were analysed for their content of total organic carbon (TOC) and elemental composition. Source rock quality was determined by Rock-Eval pyrolysis. Reflected light microscopy was used to analyse the organic matter (maceral) composition of the rocks, and the thermal maturity was determined by vitrinite reflectance (VR) measurements. In addition to the 56 samples, VR measurements were carried out in three wells from two oil-producing basins and VR gradients were constructed. Rock-Eval screening data from one of the wells is also presented. The oil shales were deposited in freshwater (to brackish) lakes with a high preservation potential (TOC contents up to 44.18 wt%). They contain abundant lamalginite and principally algal-derived fluorescing amorphous organic matter followed by liptodetrinite and telalginite (Botryococcus-type). Huminite may be present in subordinate amounts. The coals are completely dominated by huminite and were formed in freshwater mires. VR values from 0.38 to 0.47%Roshow that the exposed coals are thermally immature. VR values from the associated oil shales are suppressed by 0.11 to 0.28%Ro. The oil shales have H/C ratios >1.43, and Hydrogen Index (HI) values are generally >400 mg HC/g TOC and may reach 704 mg HC/gTOC. In general, the coals have H/C ratios between about 0.80 and 0.90, and the HI values vary considerably from approximately 50 to 300 mg HC/gTOC. The HI max of the coals, which represent the true source rock potential, range from ∼160 to 310 mg HC/g TOC indicating a potential for oil/gas and oil generation. The steep VR curves from the oil-producing basins reflect high geothermal gradients of ∼62°C/km and ∼92°C/km. The depth to the top oil window for the oil shales at a VR of ∼0.70%R o is determined to be between ∼1100 m and 1800 m depending on the geothermal gradient. The kerogen composition of the oil shales and the high geothermal gradients result in narrow oil windows, possibly spanning only ∼300 to 400 m in the warmest basins. The effective oil window of the coals is estimated to start from ∼0.82 to 0.98%Roand burial depths of ∼1300 to 1400 m (∼92°C/km) and ∼2100 to 2300 m (∼62°C/km) are necessary for efficient oil expulsion to occur. © 2006 Scientific Press Ltd.